INVENTORY HANDPHONE PRE PAID PULSA CONTENT IN KIOS FRIENDLY CELLULAR BY USING MICROSOFT VISUAL BASIC 6.0 - Suwandi Suwandi (Jurnal Sistem Informasi, 2008)
This writing describes the sale of prepaid applications on Cel lular Friendly Kiosk to mas ih using manual recording, so the risk of error. Therefore authors provide a better alternative and efficient by making the application of the computerized sales by using programming language Visual Basic 6.0 that add writers to assist in the processing of the data until it reports.